Question:

Determine f-1(x) for f(x)= cubed root of x-3?

by  |  earlier

0 LIKES UnLike

Determine f-1(x) for f(x)= cubed root of x-3?

 Tags:

   Report

2 ANSWERS


  1. f inverse??

    y= cubed root of( x-3)

    swap x and y

    x= cubed root of (y-3)

    cube both sides

    x^3 = y-3

    x^3 +3 = y   ===> f inverse


  2. f(x) = ³V (x - 3)

    y = ³V(x - 3)

    y³ = x - 3

    y³ + 3 = x

    --> f-1(x) = x³ + 3

    Alejandra

Question Stats

Latest activity: earlier.
This question has 2 answers.

BECOME A GUIDE

Share your knowledge and help people by answering questions.